Charcot, Mitchell and Lees: neurology free thinkers and their experiences of psychoactive drugs - Hélio A. G. Teive; Francisco M.B. Germiniani; Pedro A. Kowacs; Renato P. Munhoz (Arquivos de Neuro-Psiquiatria)
ABSTRACT Three world-famous neurologists, Charcot and Mitchell, in the 19th century, and Lees, in this century, all of whom had great scientific curiosity, experimented with the psychoactive drugs hashish, mescal and yagé, respectively, in an attempt to increase their knowledge of neurological diseases and how the brain works.